C20-C21-C23 tricyclic terpanes abundance patterns: Origin and application to depositional environment identification - Wang, Aiguo; Li, Chunyu; Li, Long; Pu, Renhai; Yang, Zeguang; Zhu, Nan; Guo, Kai (Frontiers in Earth Science, 2023)
Reconstruction of paleo-depositional environments in a sedimentary basin is often obstructed by the absence of typical environmental indicators in sedimentary rocks. Here, we propose a biomarker method using C20-C21-C23 tricyclic terpanes (TTs) as a tracer, which is simple in analysis but robust to provide reliable and detailed environmental information. Based on the analysis of 271 C20-C21-C23TT data from 32 basins in 18 countries, we observed a relationship between C20-C21-C23TT abundance patterns and depositional environments. This relationship was attributed to the control of depositional environments on the input proportions of plankton and terrigenous plants, which act as two end-member precursors for the TTs in a depositional system. The various mixing proportions between these two end-members result in different C20-C21-C23TT abundance patterns associated with different depositional environments, e.g., C20>C21>C23TT in river-lake transitional, C20<C21<C23TT in marine or saline lacustrine environments, C20<C21>C23TT in freshwater lacustrine and C20>C21<C23TT in marine-continental transitional environments. In addition, the C23/C21TT ratio increases with elevated salinity of depositional water, and the C21/C20TT ratio increases with increasing water depths. Based on these observations, a discrimination diagram using C23/C21TT vs. C21/C20TT was developed for environmental identification. The validity of this C20-C21-C23TT biomarker method is well demonstrated by the rock samples with typical environmental indicators. This method is applicable in a broad spectrum of rocks and in maturities up to 2.4%Ro. Its strength was shown by a case study of a complex depositional system in the East China Sea Basin, which has been strongly affected by eustasy.